Penciptaan Keteng-Keteng Elektrik Telu Ngawan - Sembiring, Adina Sastra; Widiastuti, Uyuni; Tarigan, Brepin (Universitas Negeri Surabaya, 2020)
Keteng-keteng is a traditional Karo music that is played by beating with two sticks. So far, keteng-ketengare made from one segment of bamboo, therefore this research creates an electric keteng-ketengtelu ngawan which is the development of one bamboo segment into three bamboo sections by adding an equalizer to the keteng-ketengso that the resulting keteng-keteng’ssound can actually be adjusted according to the color of the sound on the middle bass and treble. The objectives of this study were to: (1) produce electric keteng-keteng telu ngawan; (2) to find out the technique of playing the electric keteng-ketengtelu ngawan; (3) to determine the musical composition of electric keteng-ketengtelu ngawan. The method used in this research is the Research & Development approach, which consists of: (1) defining the concept of creating electric keteng-keteng telu ngawan; (2) Creation of electric keteng-ketengtelu ngawan; (3) validation by experts, namely traditional Karo music artists. With the creation of electric keteng-keteng telu ngawan, it can minimize keteng-keteng play and produce Electric Keteng-Keteng Telu Ngawan sound with three different characters, namely high, midle and low characters. From this combination, two different gung characters were found because berunausesvibrating aids, while Daluna did not use vibrating aids.Keywords: Creation, Keteng-Keteng, Electric, Telu Ngawan.